2014
DOI: 10.1007/s12035-014-9044-7
|View full text |Cite
|
Sign up to set email alerts
|

Dentate Gyrus Local Circuit is Implicated in Learning Under Stress—a Role for Neurofascin

Abstract: The inhibitory synapses at the axon initial segment (AIS) of dentate gyrus granular cells are almost exclusively innervated by the axo-axonic chandelier interneurons. However, the role of chandelier neurons in local circuitry is poorly understood and controversially discussed. The cell adhesion molecule neurofascin is specifically expressed at the AIS. It is crucially required for the stabilization of axo-axonic synapses. Knockdown of neurofascin is therefore a convenient tool to interfere with chandelier inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…A second example is the use of neurofascin to specifically modulate feed-back inhibition onto the DG by axo-axonic chandelier interneurons without affecting feed forward inhibition. The authors took advantage of restricted expression of neurofascin in the axon initial segment that is primarily innervated by axo-axonic chandelier interneurons and found that downregulation of neurofascin decreased feed-back inhibition onto the DG to impair learning (Zitman et al, 2014).…”
Section: Re-engineering Intrinsic and Extrinsic Connectivity Of The Dmentioning
confidence: 99%
“…A second example is the use of neurofascin to specifically modulate feed-back inhibition onto the DG by axo-axonic chandelier interneurons without affecting feed forward inhibition. The authors took advantage of restricted expression of neurofascin in the axon initial segment that is primarily innervated by axo-axonic chandelier interneurons and found that downregulation of neurofascin decreased feed-back inhibition onto the DG to impair learning (Zitman et al, 2014).…”
Section: Re-engineering Intrinsic and Extrinsic Connectivity Of The Dmentioning
confidence: 99%
“…One possibility to control GABAergic inhibitory transmission of AACs emerges by manipulating neurofascin (NF) (Kriebel et al , 2011; Zitman et al , 2014). Neurofascin is a cell adhesion molecule belonging to the L1 subfamily of immunoglobulins (Kriebel et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There, NF has been implicated in maintaining action potential initiation (Zonta et al , 2011) and in stabilizing inhibitory synapses by regulating the postsynaptic scaffold protein gephyrin (Burkarth et al , 2007; Kriebel et al , 2011). Knockdown of NF at the AIS decreased gephyrin clustering, which was associated with reduced expression of the GABA A receptor subunit β 2/3 at the postsynaptic site and GAD65 at the inhibitory presynapse (Zitman et al , 2014). Within the dentate gyrus (DG), such a modulation of GABAergic inhibitory transmission at the AIS via NF knockdown altered feedback inhibition measured by paired-pulse stimulation while feed-forward inhibition remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cortex, the axonal "cartridges" of synaptic boutons that form onto the AIS are generally found on the more distal AIS domain, where the AP is thought to initiate (9). Although there is little information on the role of these interneurons in network function, they have been implicated in a number of events, including driving negative feedback in the dentate gyrus (10), modulating the emergence of sharp waves in the hippocampus (11), providing complex inhibitory-excitatory feedforward loops in the cortex (12), as well as shunting and filtering out APs backpropagating from ectopic initiation sites in the hippocampus (13). In addition, there is an ongoing debate as to whether axoaxonic synapses depolarize or hyperpolarize postsynaptic pyramidal neurons (14), although in conditions mimicking in vivo-like oscillations, they act mainly as inhibitors of excitability (15).…”
mentioning
confidence: 99%